Electrode for battery, battery and method for manufacturing electrode for battery

By forming a two-layer structure on the negative active material layer of the battery electrode, the amount of adhesive on the lower side of the substrate is reduced and the amount of adhesive on the upper side is increased. Combined with the method of magnetic field-oriented graphite, the problem of insufficient battery rate performance is solved, and better cycle performance and rate performance are achieved.

CN119812190APending Publication Date: 2025-04-11TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411399261.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-11
Filing Date
2024-10-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing battery electrodes have shortcomings in terms of rate performance, especially due to performance problems caused by low ion diffusion.

Method used

By reducing the adhesive on the lower side of the substrate of the negative electrode active material layer, the adhesion between the substrate and the negative electrode active material layer is reduced, boundary stress concentration is alleviated, and adhesive is added on the upper side to promote the diffusion of ions. The specific implementation method includes forming a negative electrode active material layer with a two-layer structure on the surface of the substrate, with a small amount of adhesive agent on the first layer and a large amount of adhesive agent on the second layer, and oriented graphite through a magnetic field to fix its orientation state.

Benefits of technology

By reducing the adhesion between the substrate and the negative electrode active material layer and increasing the ion diffusion, the cycle performance and rate performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812190A_ABST
    Figure CN119812190A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode for a battery, a battery, and a method for manufacturing the electrode for the battery. The purpose of the present disclosure is to improve rate capability. An electrode for a battery according to the present disclosure includes a substrate and a negative electrode active material layer. The negative electrode active material layer is disposed on the surface of the substrate. The negative electrode active material layer contains graphite and a binder. A first layer and a second layer are formed in the negative electrode active material layer. The first layer is formed between the substrate and the second layer. 1.2 < = A < = 4 and 1lt are satisfied; m < 2 > / m1 ''and'' 1lt; [theta] 2 / [theta] 1 ". A represents the aspect ratio of graphite. And m1 represents the mass fraction of the adhesive in the first layer. And m2 represents the mass fraction of the binder in the second layer. And theta1 represents the orientation angle of the graphite in the first layer. And theta2 represents the orientation angle of the graphite in the second layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a battery electrode, a battery, and a method for producing the battery electrode. Background Art

[0002] Japanese Patent Application Laid-Open No. 2014-096201 discloses a negative electrode active material layer in which the amount of binder is small on the side close to the metal foil. Summary of the invention

[0003] By reducing the adhesive on the side (lower side) close to the substrate, the adhesion between the substrate and the negative electrode active material layer can be reduced. By reducing the adhesion, the stress concentration at the boundary between the substrate and the negative electrode active material layer can be relaxed. As a result, for example, an improvement in cycle performance can be expected.

[0004] On the other hand, the ion diffusivity tends to be low on the upper side of the negative electrode active material layer where the binder is relatively large. Since the ion diffusivity is low on the upper side, the expected rate performance may not be obtained.

[0005] The present disclosure aims to improve rate performance.

[0006] The following describes the technical structure and effects of the present disclosure. However, the mechanism of action includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.

[0007] 1. A battery electrode, comprising a substrate and a negative electrode active material layer. The negative electrode active material layer is disposed on a surface of the substrate. The negative electrode active material layer comprises graphite and a binder. A first layer and a second layer are formed in the negative electrode active material layer. The first layer is formed between the substrate and the second layer. The battery electrode satisfies the relationship of the following formulas (1) to (3).

[0008] 1.2 ≤ A≤ 4 (1)

[0009] 1 < m2 / m1 (2)

[0010] 1 < θ2 / θ1 (3)

[0011] In the above formulas (1) to (3), A represents the aspect ratio of graphite. m1 represents the mass fraction of the binder in the first layer. m2 represents the mass fraction of the binder in the second layer. θ1 represents the orientation angle of graphite in the first layer. θ2 represents the orientation angle of graphite in the second layer.

[0012] As shown in the above formula (3), in the second layer (upper layer), graphite is more strongly oriented than in the first layer (lower layer). That is, the major axis of the graphite is along the thickness direction. In the second layer, the strong orientation of the graphite can promote the diffusion of ions in the thickness direction. Therefore, as shown in the above formula (2), even if the binder in the second layer is large, the rate performance can be expected to be improved.

[0013] On the other hand, in the first layer, the major axis of the graphite is along the surface of the substrate. By increasing the contact area between the graphite and the substrate, it can be expected that the negative electrode active material layer and the substrate are fully adhered by a small amount of adhesive. Furthermore, in the first layer, there is little adhesive, which can be expected to promote the diffusion of ions.

[0014] As shown in the above formula (1), the aspect ratio of graphite is 1.2 to 4. When the aspect ratio is less than 1.2, the expected rate performance may not be obtained even if the graphite is oriented. Even if the aspect ratio exceeds 4, sufficient ion diffusivity may not be obtained. Generally speaking, the negative electrode active material layer is manufactured by pressing. Particles with a large aspect ratio are pressed while being oriented in the thickness direction, thereby, for example, the frequency of cracking and crushing of the particles may increase. Cracking of particles in the second layer (upper layer) may reduce the reaction area. Due to the reduction in the reaction area, the expected rate performance may not be obtained.

[0015] During the pressing process, the first layer (lower layer) can function as a buffer. This is because the amount of adhesive in the first layer is small. By having the first layer function as a buffer, the load applied to the second layer (upper layer) during the pressing process can be mitigated. By mitigating the load, it is expected that the orientation state of the second layer will not collapse easily. Moreover, the amount of adhesive in the second layer is large, so it is expected that the orientation state of the second layer will be firmly fixed.

[0016] 2. The battery electrode described in the above “1” may also include the following configuration, for example. The battery electrode further satisfies the relationship of the following formula (4).

[0017] 0.02 ≤ I 110 / I 002 (4)

[0018] In the above formula (4), I 110 It represents the diffraction intensity of the (110) plane in the X-ray diffraction pattern of the negative electrode active material layer. 002 It shows the diffraction intensity of the (002) plane in the X-ray diffraction pattern of the negative electrode active material layer.

[0019] The intensity ratio (I 110 / I 002 ) is an indicator of the orientation state of graphite. 110 / I 002 The larger the I is, the closer the long axis of the graphite is to the thickness direction. 110 / I 002 This reflects the average value of the orientation state of the first layer and the orientation state of the second layer.

[0020] 3. The battery electrode described in the above “1” or “2” may also have the following configuration, for example: The thickness of the negative electrode active material layer is 100 to 400 μm.

[0021] The above-mentioned technique of "1" is suitable for thick negative electrode active material layers, especially negative electrode active material layers with a thickness of 100 μm or more. When the thickness of the negative electrode active material layer is 400 μm or less, the balance between rate performance and capacity is good.

[0022] 4. The battery electrode according to any one of the above "1" to "3" may include, for example, the following configuration. The battery electrode further satisfies the relationship of the following formula (5).

[0023] 0.1 ≤ T1 / (T1+T2) ≤ 0.4 (5)

[0024] In the above formula (5), T1 represents the thickness of the first layer, and T2 represents the thickness of the second layer.

[0025] When the relationship of the above formula (5) is satisfied, improvement in rate performance can be expected.

[0026] 5. A battery comprising the battery electrode described in any one of "1" to "4" above.

[0027] 6. A method for producing a battery electrode, comprising the following steps (a) to (d) in order.

[0028] Step (a): The first layer is formed by applying the first slurry on the surface of the substrate.

[0029] Step (b): The second layer is formed by applying the second slurry on the first layer.

[0030] Step (c): Applying a magnetic field to the first layer and the second layer.

[0031] Step (d): Drying the first layer and the second layer to form a negative electrode active material layer.

[0032] The first slurry and the second slurry each contain graphite, a binder, and a dispersion medium.

[0033] The production method satisfies the relationship between the following equations (6) and (7).

[0034] 2 < η1 / η2 (6)

[0035] 1 < r2 / r1 (7)

[0036] In the above formulas (6) and (7), η1 represents the viscosity of the first slurry. η2 represents the viscosity of the second slurry. r1 represents the mixing ratio of the binder in the solid content of the first slurry. r2 represents the mixing ratio of the binder in the solid content of the second slurry.

[0037] By applying a magnetic field to the slurry containing graphite, the graphite can be oriented. Since the viscosity of the second slurry is lower than that of the first slurry, it is expected that the orientation angle of the second layer becomes larger than the orientation angle of the first layer. Moreover, since the mixing ratio of the binder in the second slurry is large, it is expected that the graphite in the second layer is fixed in an oriented state.

[0038] The following describes an embodiment of the present disclosure (hereinafter referred to as "the present embodiment"). However, the present embodiment does not limit the technical scope of the present disclosure. The present embodiment is illustrative in all aspects. The present embodiment is non-restrictive. The technical scope of the present disclosure includes all changes within the meaning and scope equivalent to the description of the scope of the claim for protection. For example, it is intended from the outset to include a solution in which any configuration is extracted from the present embodiment and any combination thereof is made.

[0039] The above and other objects, features, aspects and advantages of the present disclosure will become more apparent from the following detailed description of the present disclosure when read in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a conceptual diagram showing a method for measuring an orientation angle.

[0041] Figure 2 This is an example of an XRD pattern.

[0042] Figure 3 It is a schematic cross-sectional view showing an example of the battery electrode according to the present embodiment.

[0043] Figure 4 It is a graph showing the relationship between the XRD intensity ratio and the binder existence ratio.

[0044] Figure 5 This is a schematic flowchart of the method for producing a battery electrode according to the present embodiment.

[0045] Figure 6 This is a conceptual diagram showing an example of a battery according to this embodiment.

[0046] Figure 7 This is a table showing the structure of the first battery.

[0047] Figure 8 This is a table showing the structure of the second battery.

[0048] Fig. 9 This is a table showing the structure of the third battery.

[0049] Fig.10 is a table showing the experimental results.

[0050] Fig.11It is a graph showing the relationship between the XRD intensity ratio and the discharge rate.

[0051] Fig.12 It is a graph showing the relationship between the aspect ratio of graphite and the discharge rate. DETAILED DESCRIPTION

[0052] <Terms and Phrases>

[0053] "Having", "including", "having" and their variations are open terms. In addition to the essential elements, an open term may or may not contain additional elements. The statement "consisting of..." is a closed term. However, even a structure expressed in a closed term usually contains incidental impurities and additional elements that are not related to the target technology. The statement "consisting essentially of..." is a semi-closed term. In a semi-closed term, it is allowed to add elements that have no substantial impact on the basic and new characteristics of the target technology.

[0054] Expressions such as "may also" and "can" are not used in the strict sense to mean "must" but to mean "there is a possibility" of allowing.

[0055] Geometric terms should not be interpreted in a strict sense. Examples of geometric terms include "parallel", "perpendicular", and "orthogonal". For example, "parallel" may slightly deviate from "parallel" in a strict sense. Geometric terms may include tolerances, errors, etc. in design, operation, and manufacturing. The dimensional relationships in the figures are sometimes inconsistent with the actual dimensional relationships. In order to help the reader understand, the dimensional relationships in the figures are sometimes changed. Sometimes some structures are omitted.

[0056] Numerical ranges such as "m to n%" include upper and lower limits unless otherwise specified. That is, "m to n%" means a numerical range of "above m% and below n%. In addition, "above m% and below n%" includes "more than m% and less than n%. "Above" and "below" are represented by an inequality sign "≤" with an equal sign. "Exceeding" and "below" are represented by an inequality sign "<" without an equal sign. A value arbitrarily selected from the numerical range may also be used as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining numerical values ​​within the numerical range with numerical values ​​recorded in other parts, tables, figures, etc. in this specification.

[0057] All numerical values ​​are modified by the term "about". The term "about" may represent, for example, ±5%, ±3%, ±1%, etc. All numerical values ​​may be approximate values ​​that may vary according to the utilization form of the technology disclosed herein. All numerical values ​​may be represented by significant figures. Unless otherwise specified, the measured value may be the average value of multiple measurements. The number of measurements may be more than 3 times, more than 5 times, or more than 10 times. Generally, it can be expected that the more the number of measurements, the higher the reliability of the average value. The measured value may be rounded off by rounding off based on the number of significant figures. The measured value may, for example, include errors associated with the detection limit of the measuring device, etc.

[0058] The "orientation angle" refers to a value measured by the following method. Figure 1 This is a conceptual diagram showing a method for measuring the orientation angle. A cross-sectional sample is prepared by cutting the negative electrode active material layer. The cross-sectional sample includes a cross section parallel to the thickness direction of the negative electrode active material layer. For example, the observation object portion may also be cleaned by a cross-sectional polisher (registered trademark) or the like. The cross-sectional sample is observed by SEM (Scanning Electron Microscope), thereby obtaining a SEM image. In the SEM image, graphite (particles) has a major axis diameter φ1 and a minor axis diameter φ2. On the contour line of graphite, the diameter connecting the two points farthest apart is the "major axis diameter". At the midpoint of the major axis diameter, the diameter orthogonal to the major axis diameter is the "minor axis diameter". The orientation angle (θ) represents the angle (acute angle side) formed by the surface of the substrate 210 and the major axis diameter. The orientation angle (θ) can take a value of 0 to 90°. Ten particles are randomly selected from the object portion (e.g., the first layer) of the SEM image. In each particle, the orientation angle is measured. The arithmetic mean of the orientation angles of the 10 particles is used.

[0059] "Aspect ratio" means the ratio of the major axis diameter φ1 to the minor axis diameter φ2 (φ1 / φ2). The aspect ratio can also be measured in the SEM image used to measure the orientation angle. Ten particles are randomly selected from the target part (e.g., the first layer) of the SEM image. The aspect ratio is measured in each particle. The arithmetic mean of the aspect ratios of the ten particles is used.

[0060] "D50" indicates the particle size when the cumulative distribution is 50% in the volume-based particle size distribution (cumulative distribution). The particle size distribution can be measured by a laser diffraction method.

[0061] "BET specific surface area" means a specific surface area measured by a gas adsorption method (BET single point method). Nitrogen was used as the adsorption gas.

[0062] The XRD pattern is measured by an XRD device. The X-ray source is CuKα radiation. The measurement range is "10°≤2θ≤90°". Figure 2This is an example of an XRD pattern. The diffraction peak of the (002) plane can be detected in the range of "25°≤2θ≤30°". The diffraction peak of the (110) plane can be detected in the range of "75°≤2θ≤80°". The diffraction intensity (I 002 ,I 110 ).

[0063] "Viscosity" is the viscosity of the sample at 25°C for 10 seconds. -1 The viscosity can be measured by a rotational viscometer. For example, a rotational viscometer described in JIS K 7117:1999 "Plastics - Liquid, emulsified or dispersed resins - Determination of viscosity at a constant shear rate using a rotational viscometer" can be used.

[0064] The "mixing ratio" of the binder in the slurry refers to the ratio of the mass of the binder to the mass of the entire solid content. The solid content refers to the components other than the dispersion medium.

[0065] The stoichiometric composition formula represents a representative example of a compound. A compound may also have a non-stoichiometric composition. For example, "Al2O3" is not limited to a compound having an amount ratio (molar ratio) of "Al / O=2 / 3". Unless otherwise specified, "Al2O3" means a compound containing Al and O in an arbitrary molar ratio. For example, trace elements may be doped into the compound. Al and O may also be partially replaced by other elements.

[0066] "Derivative" means a compound that has been changed in a part of a compound as a parent by at least one selected from the group consisting of the introduction of a substituent, replacement of atoms, oxidation, reduction and other chemical reactions. The change site may be one or more. "Substituent" may include, for example, at least one selected from the group consisting of alkyl, alkenyl, alkynyl, cycloalkyl, unsaturated cycloalkyl, aryl, heterocyclic, halogen (F, Cl, Br, I, etc.), OH, SH, CN, SCN, OCN, nitro, alkoxy, unsaturated alkoxy, amino, alkylamino, dialkylamino, aryloxy, acyl, alkoxycarbonyl, acyloxy, aryloxycarbonyl, acylamino, alkoxycarbonylamino, aryloxycarbonylamino, sulfonylamino, sulfamoyl, carbamoyl, alkylthio, arylthio, sulfonyl, sulfinyl, urea, phosphoramido, sulfo, carboxyl, hydroxamic acid, sulfinyl, hydrazine, imino and silyl. These substituents may be further substituted. When there are two or more substituents, the substituents may be the same or different. Multiple substituents may be combined to form a ring. Furthermore, a derivative of a polymer compound (resin material) may also be referred to as a "modified product".

[0067] The "copolymer" includes at least one selected from the group consisting of unspecified type, statistical type, random type, alternating type, periodic type, block type and graft type.

[0068] <Battery Electrodes>

[0069] Hereinafter, the battery electrode may be referred to as "electrode". The electrode is in sheet form. As long as the electrode is for battery, it can be applied to any purpose. For example, the electrode can be for monopolar battery (single electrode battery), bipolar battery, non-aqueous battery, lithium ion battery, etc.

[0070] Figure 3 2 is a schematic cross-sectional view showing an example of a battery electrode according to the present embodiment. The electrode 200 may be, for example, a negative electrode of a monopolar lithium ion battery. Figure 1 The cross section is parallel to the thickness direction (Z direction) of the electrode 200 . The electrode 200 includes a substrate 210 and a negative electrode active material layer 220 .

[0071] The substrate 210 supports the negative electrode active material layer 220. The substrate 210 may be, for example, in a sheet shape. The thickness of the substrate 210 may be, for example, any one of 1 to 50 μm, 3 to 30 μm, and 5 to 15 μm. The substrate 210 has conductivity. The substrate 210 may include, for example, a metal foil, etc. The substrate 210 may include, for example, at least one selected from Cu, Ni, Zn, Pb, Al, Ti, Fe, Ag, Au, and a conductive resin. The substrate 210 may include, for example, Cu foil, Cu alloy foil, etc. The substrate 210 may have, for example, a multilayer structure. For example, the substrate 210 may be formed by laminating Cu foil and Al foil.

[0072] The negative electrode active material layer 220 is arranged on the surface of the substrate 210. The negative electrode active material layer 220 may be arranged only on one side of the substrate 210. The negative electrode active material layer 220 may also be arranged on both sides of the substrate 210. When the electrode 200 is for a bipolar battery, the negative electrode active material layer 220 may be arranged on one side (front side) of the substrate 210, and the positive electrode active material layer (not shown) may be arranged on the other side (back side). The thickness of the negative electrode active material layer 220 may be, for example, any one of 10 μm or more, 50 μm or more, 100 μm or more, 150 μm or more, 200 μm or more, 300 μm or more, 400 μm or more, and 500 μm or more. The thickness of the negative electrode active material layer 220 may also be any one of 1000 μm or less, 500 μm or less, 400 μm or less, 300 μm or less, and 200 μm or less. The thickness of the negative electrode active material layer 220 may be, for example, 100 to 400 μm.

[0073] A first layer 221 and a second layer 222 are formed in the negative electrode active material layer 220. The first layer 221 is a lower layer. The first layer 221 is formed between the substrate 210 and the second layer 222. The first layer 221 may be in direct contact with the substrate 210. The first layer 221 may also include an interface between the substrate 210 and the negative electrode active material layer 220. The second layer 222 is an upper layer. The second layer 222 may also be directly stacked on the first layer 221. The second layer 222 may also include the surface of the negative electrode active material layer 220. The orientation state of the graphite 10 is different between the first layer 221 and the second layer 222. Moreover, the amount of the binder 20 is different between the first layer 221 and the second layer 222.

[0074] The thickness (T1) of the first layer 221 and the thickness (T2) of the second layer 222 may satisfy the following relationship (5), for example.

[0075] 0.1 ≤ T1 / (T1+T2) ≤ 0.4 (5)

[0076] The thickness ratio (T1 / (T1+T2)) may be, for example, 0.2 or more or 0.3 or more. The thickness ratio (T1 / (T1+T2)) may be, for example, 0.3 or less or 0.2 or less.

[0077] The negative electrode active material layer 220 includes a negative electrode active material and a binder. The negative electrode active material can cause a negative electrode reaction. The negative electrode active material includes graphite. Graphite may also include at least one selected from artificial graphite and natural graphite. For example, the surface of graphite may also be covered with amorphous carbon. As long as the negative electrode active material includes graphite, it may further include other negative electrode active materials. In addition to graphite, the negative electrode active material may also include at least one selected from silicon (Si), silicon oxide (SiO), silicon-carbon composite material (Si-C), silicon-based alloy, tin, tin oxide and lithium titanate. For example, Si-C may also be formed by dispersing Si particles in carbon particles. The mass fraction of graphite relative to the total of the negative electrode active material may also be, for example, any one of 50% or more, 60% or more, 70% or more, 80% or more, 90% or more and 95% or more.

[0078] Graphite is a particle group (powder). The D50 of graphite may be, for example, 1 to 50 μm, 5 to 30 μm, or 10 to 25 μm. The BET specific surface area of ​​graphite may be, for example, 0.5 to 5 m 2 / g, 1~4m 2 / g and 1.5~3m 2 / g.

[0079] The aspect ratio (A) of graphite is 1.2 to 4. That is, the relationship of the following formula (1) is satisfied.

[0080] 1.2 ≤ A≤ 4 (1)

[0081] The aspect ratio (A) may be, for example, 1.5 or more, 2 or more, 2.5 or more, 3 or more, or 3.5 or more. The aspect ratio (A) may be, for example, 3.8 or less, 3.5 or less, 3 or less, 2.5 or less, 2 or less, or 1.5 or less.

[0082] In the first layer 221 and the second layer 222, graphite has a specific orientation state, that is, it satisfies the relationship of the following formula (3).

[0083] 1 < θ2 / θ1 (3)

[0084] The orientation angle (θ1) in the first layer 221 may be, for example, any one of 0° or more, 5° or more, 10° or more, and 20° or more. The orientation angle (θ1) may be, for example, any one of 30° or less, 20° or less, 10° or less, and 5° or less. The orientation angle (θ2) in the second layer 222 may be, for example, any one of 60° or more, 70° or more, and 80° or more. The orientation angle (θ2) may be, for example, any one of 90° or less, 80° or less, and 70° or less. The orientation angle ratio (θ2 / θ1) may be, for example, any one of 1.1 or more, 1.5 or more, 2 or more, 5 or more, 10 or more, 30 or more, 50 or more, and 100 or more. The orientation angle ratio (θ2 / θ1) may be, for example, any one of 1000 or less, 500 or less, 100 or less, 50 or less, 30 or less, and 10 or less.

[0085] The relationship of the following formula (4) may also be satisfied.

[0086] 0.02 ≤ I 110 / I 002 (4)

[0087] It is believed that the XRD intensity ratio (I 110 / I 002 ) reflects the average value of the orientation state of the first layer 221 and the second layer 222. XRD intensity ratio (I 110 / I 002 ) may be, for example, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, or 0.08 or more. XRD intensity ratio (I 110 / I 002 ) For example, it can also be any one of less than 0.10, less than 0.09, less than 0.08, less than 0.07, less than 0.06, less than 0.05, less than 0.04 and less than 0.03.

[0088] The binder binds solids to each other. The binder may contain optional components. For example, the binder may also contain at least one selected from styrene butadiene rubber (SBR), acrylic butadiene rubber (ABR), polyacrylonitrile (PAN), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), acrylic resin (acrylic ester copolymer), methacrylic resin (methacrylic ester copolymer), polyvinyl alcohol (PVA) and their derivatives. The amount of the binder to be added may be, for example, any one of 0.1 to 10 parts by mass, 0.5 to 5 parts by mass, 1 to 4 parts by mass and 2 to 3 parts by mass relative to 100 parts by mass of the negative electrode active material.

[0089] The negative electrode active material layer 220 may also include a thickener. The thickener can give viscosity to the slurry. The thickener may include, for example, at least one selected from sodium alginate, carboxymethyl cellulose (CMC), polyacrylic acid (PAA) and polyvinyl pyrrolidone (PVP). CMC and PAA, etc., may also be in the form of Na salt, Li salt, NH4 salt, etc. The amount of the thickener may be, for example, any one of 0.1 to 2 parts by mass, 0.1 to 1 part by mass and 0.1 to 0.5 parts by mass relative to 100 parts by mass of the negative electrode active material.

[0090] The negative electrode active material layer 220 may also include a conductive material. The conductive material can form an electron conduction path in the negative electrode active material layer 220. The conductive material may also include, for example, at least one selected from acetylene black (AB), Ketjen black (registered trademark), vapor grown carbon fiber (VGCF), carbon nanotube (CNT) and graphene sheet (GF). CNT may also include at least one selected from single-walled CNT (SWCNT) and multi-walled CNT (MWCNT). The amount of the conductive material may be, for example, 0.1 to 10 parts by mass relative to 100 parts by mass of the negative electrode active material.

[0091] The negative electrode active material layer 220 may also include, for example, an inorganic filler, an organic filler, a solid electrolyte, a surface modifier, a dispersant, a lubricant, a flame retardant, a protective agent, a flux, a coupling agent, an adsorbent, etc. The negative electrode active material layer 220 may also include, for example, a layered silicate (smectite, montmorillonite, bentonite, hectorite, etc.), an inorganic filler (solid alumina, hollow silica, boehmite, etc.), a polysiloxane compound, etc.

[0092] The first layer 221 and the second layer 222 satisfy the relationship of the following formula (2).

[0093] 1 < m2 / m1 (2)

[0094] The mass fraction (m1) of the binder in the first layer 221 may be, for example, any one of 0.5 to 2.5%, 1 to 2%, and 1 to 1.5%. The mass fraction (m2) of the binder in the second layer 222 may be, for example, any one of 1 to 5%, 1.5 to 3%, and 1.5 to 2%. The binder presence ratio (m2 / m1) in the first layer 221 and the second layer 222 may be, for example, any one of 1.2 or more, 1.5 or more, 2 or more, 2.5 or more, and 3 or more. The binder presence ratio (m2 / m1) may be any one of 5 or less, 4 or less, 3 or less, 2.5 or less, 2 or less, and 1.5 or less.

[0095] The existence ratio of the binder (m2 / m1) exceeding 1 can also be confirmed by, for example, mapping analysis based on SEM-EDX (Scanning Electron Microscope-Energy dispersive X-ray spectrometry). For example, the dyeing treatment of the binder can also be implemented in the cross-sectional sample of the negative electrode active material layer 220. For example, SBR can also be stained with osmium oxide. In the cross-sectional sample, the mapping analysis of the binder is performed. For example, in the first layer 221, the pixels corresponding to the binder are counted. The area fraction (S1) of the binder in the first layer 221 is calculated by dividing the number of pixels corresponding to the binder by the number of pixels in the first layer 221 as a whole. Similarly, the area fraction (S2) of the binder in the second layer 222 is calculated. It is considered that the area fraction ratio (S2 / S1) is substantially equal to the existence ratio (m2 / m1) of the binder.

[0096] Figure 4 It is a coordinate diagram showing the relationship between the XRD intensity ratio and the binder presence ratio. By applying a magnetic field to the slurry coating, the XRD intensity ratio can be increased. The hollow circle (1 point) is a coating formed by a single slurry. The use of a single slurry indicates that the negative electrode active material layer 220 has a single-layer structure. In the black circle (3 points), two slurries with different viscosities are used. The use of two slurries indicates that the negative electrode active material layer 220 has a double-layer structure. Compared with the single-layer structure, the double-layer structure has a tendency that the XRD intensity ratio is easy to increase. Moreover, in the double-layer structure, the XRD intensity ratio tends to increase further by increasing the binder presence ratio. It is believed that this is because the lower layer acts as a buffer during pressing, and thus the orientation state is not easily destroyed.

[0097] <Method for producing battery electrode>

[0098] Figure 5: is a schematic flow chart of the manufacturing method of the battery electrode of the present embodiment. Hereinafter, the "manufacturing method of the battery electrode of the present embodiment" may be referred to as the "present manufacturing method". The present manufacturing method sequentially comprises "(a) formation of the first layer", "(b) formation of the second layer", "(c) magnetic field orientation" and "(d) drying". The present manufacturing method may also comprise, for example, "(e) compression" and the like.

[0099] (a) Formation of the first layer

[0100] The manufacturing method includes forming the first layer 221 by applying the first slurry to the surface of the substrate 210. The first slurry includes graphite, a binder and a dispersion medium. For example, the first slurry can also be formed by mixing graphite, a binder, a thickener and a dispersion medium. Any mixing device can be used. For example, a planetary mixer can also be used. The viscosity of the slurry can be adjusted by, for example, the solid content concentration, the amount of the thickener, the stirring speed and the mixing time. The viscosity of the first slurry can also be, for example, any one of 15000 mPa·s or more, 20000 mPa·s or more, 25000 mPa·s or more and 30000 mPa·s or more. The viscosity of the first slurry can also be, for example, any one of 40000 mPa·s or less, 35000 mPa·s or less, 30000 mPa·s or less and 25000 mPa·s or less.

[0101] The first layer 221 (coating film) can be formed by coating the first slurry on the surface of the substrate 210. Any coating device can be used. For example, a die coater, a roll coater, etc. can also be used. The graphite contained in the first slurry tends to be oriented along the surface of the substrate 210.

[0102] (b) Formation of the second layer

[0103] The manufacturing method includes forming the second layer 222 by applying the second slurry on the first layer 221. The second slurry includes graphite, a binder, and a dispersion medium. For example, the second slurry may be formed by mixing graphite, a binder, a thickener, and a dispersion medium.

[0104] The viscosity of the second slurry may be, for example, 5000 mPa·s or more, 10000 mPa·s or more, or 15000 mPa·s or less. The viscosity of the second slurry may be, for example, 20000 mPa·s or less, 15000 mPa·s or less, or 10000 mPa·s or less.

[0105] In the present production method, the viscosity (η1) of the first slurry and the viscosity (η2) of the second slurry satisfy the relationship of the following formula (6).

[0106] 2 < η1 / η2 (6)

[0107] The viscosity ratio (η1 / η2) may be, for example, 2.08 or more, 2.5 or more, or 3 or more. The viscosity ratio (η1 / η2) may be, for example, 5 or less, 4 or less, 3 or less, or 2.5 or less.

[0108] In the present production method, the mixing ratio (r1) of the binder in the solid content of the first slurry and the mixing ratio (r2) of the binder in the solid content of the second slurry satisfy the relationship of the following formula (7).

[0109] 1 < r2 / r1 (7)

[0110] "r2 / r1" in the above formula (7) is substantially equal to "m2 / m1" in the above formula (2).

[0111] The second layer 222 (coating film) can be formed by coating the second slurry on the first layer 221. At this stage, the first layer 221 and the second layer 222 are in a wet state. That is, the first layer 221 and the second layer 222 contain a dispersion medium.

[0112] (c) Magnetic field orientation

[0113] The manufacturing method includes applying a magnetic field to the first layer 221 and the second layer 222. For example, the magnetic field can be applied along the thickness direction of the first layer 221 and the second layer 222. The graphite contained in the first layer 221 and the second layer 222 can be oriented according to the magnetic field. Since the viscosity of the first layer 221 (the first slurry) is higher than the viscosity of the second layer 222 (the second slurry), it is considered that the graphite in the first layer 221 is difficult to orient compared with the graphite in the second layer 222. As a result, it is considered that a difference in orientation state occurs between the first layer 221 and the second layer 222. That is, in the first layer 221, graphite is easily oriented in the plane direction (XY direction). On the other hand, in the second layer 222, graphite is easily oriented in the thickness direction (Z direction). The magnetic flux density and application time of the magnetic field can be adjusted to obtain the desired orientation state. The magnetic flux density can also be, for example, 100 to 1000 mT. The application time can also be, for example, 1 to 60 minutes.

[0114] (d) Drying

[0115] The manufacturing method includes forming the negative electrode active material layer 220 by drying the first layer 221 and the second layer 222. The dispersion medium can be removed by drying. Any drying device can be used. For example, a hot air drying device can also be used. The drying temperature can also be, for example, 40 to 80° C. or 40 to 60° C. The electrode 200 can be manufactured by removing the dispersion medium.

[0116] (e) Compression

[0117] The manufacturing method may also include, for example, compressing the negative electrode active material layer 220. For example, the negative electrode active material layer 220 may also be compressed by a calender or the like. By setting the aspect ratio of the graphite to be 4 or less, cracking and crushing of the graphite on the surface of the negative electrode active material layer 220 (the second layer 222) can be reduced. Furthermore, it is believed that by configuring more binder in the second layer 222, the orientation state of the graphite can be maintained during compression.

[0118] For example, the negative electrode active material layer 220 may be compressed so that the density (apparent density) of the negative electrode active material layer 220 becomes 1.30 g / cm 3 Below. Through density is 1.30g / cm 3 The density may be, for example, 1.25 g / cm 3 Below, 1.2g / cm 3 Below and 1.15g / cm 3 The density may be, for example, 1.05 g / cm 3 Above, 1.10g / cm 3 Above and 1.15g / cm 3 Any of the above. The electrode 200 may also be cut into a predetermined size after being compressed.

[0119] <Battery>

[0120] Figure 6 1 is a conceptual diagram showing an example of a battery according to the present embodiment. Battery 1000 may be, for example, a monopolar lithium ion battery. Battery 1000 includes an outer casing 900. Outer casing 900 accommodates power generation element 500 and an electrolyte solution (not shown).

[0121] <Exterior body>

[0122] The outer casing 900 may have any form. The outer casing 900 may be, for example, a metal shell, a soft package made of a laminated film, etc. The shell may have any shape. The shell may be, for example, cylindrical, square, flat, coin-shaped, etc. The outer casing 900 may also contain, for example, Al, etc. The outer casing 900 may also accommodate, for example, one or more power generation elements 500. For example, a plurality of power generation elements 500 may also form a series circuit or a parallel circuit. In the outer casing 900, a plurality of power generation elements 500 may also be stacked in the thickness direction of the battery 1000.

[0123] <Power Generation Element>

[0124] The power generation element 500 may also be referred to as an "electrode group", "electrode body", etc. The power generation element 500 includes an electrode 200 and a counter electrode 100. In the present embodiment, the electrode 200 is a negative electrode. The counter electrode 100 is a positive electrode. The power generation element 500 may also include a separator 300. The separator 300 is arranged between the positive electrode and the negative electrode. The power generation element 500 may have any form. The power generation element 500 may also be, for example, a stacked type. For example, the power generation element 500 may also be formed by sandwiching a separator 300 between the positive electrode and the negative electrode, and alternately stacking the positive electrode and the negative electrode. The power generation element 500 may also be, for example, a wound type. For example, a stacked body may be formed by stacking a strip-shaped positive electrode, a strip-shaped separator 300, and a strip-shaped negative electrode. The power generation element 500 may also be formed by winding the stacked body into a spiral shape. The wound power generation element 500 may also be formed into a flat shape after winding.

[0125] <Positive electrode>

[0126] The positive electrode is in sheet form. The positive electrode may also include a substrate and a positive electrode active material layer. The substrate is conductive. The substrate supports the positive electrode active material layer. The substrate may also be in sheet form, for example. The thickness of the substrate may also be, for example, 5 to 50 μm. The substrate may also include, for example, a metal foil. The substrate may also include, for example, at least one selected from Al, Mn, Ti, Fe and Cr. The substrate may also include, for example, Al foil, Al alloy foil, Ti foil, stainless steel (SUS) foil, etc.

[0127] An intermediate layer may be formed between the substrate and the positive electrode active material layer. The intermediate layer does not contain the positive electrode active material. The thickness of the intermediate layer may be, for example, 0.1 to 5 μm. The intermediate layer may include, for example, a conductive material, an insulating material, an adhesive, etc. The conductive material may include, for example, carbon black, etc. The insulating material may include, for example, aluminum oxide, boehmite, aluminum hydroxide, etc. The adhesive may include, for example, PVdF, etc.

[0128] The positive electrode active material layer is arranged on the surface of the substrate. The positive electrode active material layer can be arranged only on one side of the substrate. The positive electrode active material layer can also be arranged on both sides of the substrate. The thickness of the positive electrode active material layer can also be, for example, any one of 10 to 1000 μm, 50 to 500 μm, and 100 to 300 μm. The positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer can also contain, for example, a conductive material and a binder.

[0129] The amount of the conductive material may be, for example, 0.1 to 10 parts by mass relative to 100 parts by mass of the positive electrode active material. The conductive material may include any optional components. The conductive material may include, for example, at least one selected from graphite, AB, Ketjen black, VGCF, CNT, and GF.

[0130] With respect to 100 parts by mass of the positive electrode active material, the compounding amount of the binder may also be, for example, 0.1 to 10 parts by mass. The binder may contain optional components. The binder also contains, for example, at least one selected from PVdF, vinylidene fluoride - hexafluoropropylene copolymer (PVdF - HFP), PTFE, CMC, PAA, PVA, PVP, polyoxyethylene alkyl ether, and their derivatives.

[0131] The positive electrode active material layer may also contain, for example, inorganic fillers, organic fillers, solid electrolytes, surface modifiers, dispersants, lubricants, flame retardants, protective agents, soldering agents, coupling agents, adsorbents, etc. The positive electrode active material layer may also contain, for example, polyoxyethylene allyl phenyl ether phosphate, zeolite, silane coupling agent, MoS2, WO3, etc.

[0132] The positive electrode active material may also be granular, for example. The D50 of the positive electrode active material may also be any one of 1 to 30 μm, 10 to 20 μm, and 1 to 10 μm, for example. The positive electrode active material may contain optional components. The positive electrode active material may also contain, for example, transition metal oxides, polyanion compounds, etc. Inside one particle (positive electrode active material), the composition may be uniform or non - uniform. For example, the composition may also be inclined from the surface of the particle to the center. The change in the composition may be continuous or discontinuous (step - like).

[0133] <Transition metal oxide (space group R - 3m)>

[0134] The transition metal oxide may have an arbitrary crystal structure. The transition metal oxide may also contain, for example, a crystal structure belonging to the space group R - 3m, etc. For example, a compound represented by the general formula "LiMO2" may have a crystal structure belonging to the space group R - 3m. The transition metal oxide may also be represented by the following formula.

[0135] Li 1-a Ni x M 1-x O2

[0136] In the above formula, the relationship of - 0.5 ≤ a ≤ 0.5 and 0 ≤ x ≤ 1 is satisfied. M may also contain, for example, at least one selected from Co, Mn, and Al. In the above formula, x may also satisfy the relationship of 0 < x ≤ 0.1, 0.1 ≤ x ≤ 0.2, 0.2 ≤ x ≤ 0.3, 0.3 ≤ x ≤ 0.4, 0.4 ≤ x ≤ 0.5, 0.5 ≤ x ≤ 0.6, 0.6 ≤ x ≤ 0.7, 0.7 ≤ x ≤ 0.8, 0.8 ≤ x ≤ 0.9, or 0.9 ≤ x ≤ 1. a may also satisfy the relationship of - 0.4 ≤ a ≤ 0.4, - 0.3 ≤ a ≤ 0.3, - 0.2 ≤ a ≤ 0.2, or - 0.1 ≤ a ≤ 0.1.

[0137] For example, the transition metal oxide may also include LiCoO2, LiMnO2, LiNi 0.9 Co 0.1 O2、LiNi 0.9 Mn 0.1 At least one of O2 and LiNiO2.

[0138] <ncm>

[0139] Transition metal oxides can also be represented, for example, by the following formula. The compound represented by the following formula can also be referred to as "NCM".

[0140] Li 1-a Ni x Co y Mn z O2

[0141] In the above formula, the relationships of -0.5 ≤ a ≤ 0.5, 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1 are satisfied. For example, x can also satisfy the relationship of 0 < x ≤ 0.1, 0.1 ≤ x ≤ 0.2, 0.2 ≤ x ≤ 0.3, 0.3 ≤ x ≤ 0.4, 0.4 ≤ x ≤ 0.5, 0.5 ≤ x ≤ 0.6, 0.6 ≤ x ≤ 0.7, 0.7 ≤ x ≤ 0.8, 0.8 ≤ x ≤ 0.9, or 0.9 ≤ x < 1. For example, y can also satisfy the relationship of 0 < y ≤ 0.1, 0.1 ≤ y ≤ 0.2, 0.2 ≤ y ≤ 0.3, 0.3 ≤ y ≤ 0.4, 0.4 ≤ y ≤ 0.5, 0.5 ≤ y ≤ 0.6, 0.6 ≤ y ≤ 0.7, 0.7 ≤ y ≤ 0.8, 0.8 ≤ y ≤ 0.9, or 0.9 ≤ y < 1. For example, z can also satisfy the relationship of 0 < z ≤ 0.1, 0.1 ≤ z ≤ 0.2, 0.2 ≤ z ≤ 0.3, 0.3 ≤ z ≤ 0.4, 0.4 ≤ z ≤ 0.5, 0.5 ≤ z ≤ 0.6, 0.6 ≤ z ≤ 0.7, 0.7 ≤ z ≤ 0.8, 0.8 ≤ z ≤ 0.9, or 0.9 ≤ z < 1.

[0142] NCM can also contain, for example, those selected from LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.4 Co 0.3 Mn 0.3 O2, LiNi 0.3 Co 0.4 Mn 0.3 O2, LiNi 0.3 Co 0.3 Mn 0.4 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.5 Co 0.3 Mn 0.2 O2, LiNi 0.5 Co 0.4 Mn 0.1 O2, LiNi 0.5 Co 0.1 Mn 0.4 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.6 Co 0.3 Mn 0.1 O2、LiNi 0.6 Co 0.1 Mn 0.3 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.7 Co 0.2 Mn 0.1 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi 0.9 Co 0.05 Mn 0.05 At least one of O2.

[0143] <nca>

[0144] Transition metal oxides can also be represented, for example, by the following formula. Compounds represented by the following formula can also be referred to as "NCA".

[0145] Li 1-a Ni x Co y Al z O2

[0146] In the above formula, the relationships of -0.5 ≤ a ≤ 0.5, 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1 are satisfied. For example, x can also satisfy the relationships of 0 < x ≤ 0.1, 0.1 ≤ x ≤ 0.2, 0.2 ≤ x ≤ 0.3, 0.3 ≤ x ≤ 0.4, 0.4 ≤ x ≤ 0.5, 0.5 ≤ x ≤ 0.6, 0.6 ≤ x ≤ 0.7, 0.7 ≤ x ≤ 0.8, 0.8 ≤ x ≤ 0.9, or 0.9 ≤ x < 1. For example, y can also satisfy the relationships of 0 < y ≤ 0.1, 0.1 ≤ y ≤ 0.2, 0.2 ≤ y ≤ 0.3, 0.3 ≤ y ≤ 0.4, 0.4 ≤ y ≤ 0.5, 0.5 ≤ y ≤ 0.6, 0.6 ≤ y ≤ 0.7, 0.7 ≤ y ≤ 0.8, 0.8 ≤ y ≤ 0.9, or 0.9 ≤ y < 1. For example, z can also satisfy the relationships of 0 < z ≤ 0.1, 0.1 ≤ z ≤ 0.2, 0.2 ≤ z ≤ 0.3, 0.3 ≤ z ≤ 0.4, 0.4 ≤ z ≤ 0.5, 0.5 ≤ z ≤ 0.6, 0.6 ≤ z ≤ 0.7, 0.7 ≤ z ≤ 0.8, 0.8 ≤ z ≤ 0.9, or 0.9 ≤ z < 1.

[0147] NCA can also contain, for example, at least one selected from LiNi 0.7 Co 0.1 Al 0.2 O2, LiNi 0.7 Co 0.2 Al 0.1 O2, LiNi 0.8 Co 0.1 Al 0.1 O2, LiNi 0.8 Co 0.17 Al 0.03 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, and LiNi 0.9 Co 0.05 Al 0.05 O2.

[0148] <Multi-component system>

[0149] The positive electrode active material may also include, for example, two or more NCMs. The positive electrode active material may also include, for example, NCM (0.6 ≤ x) and NCM (x < 0.6). "NCM (0.6 ≤ x)" means that in the above formula "Li 1-a Ni x Co y Mn z O2", a compound in which x (Ni ratio) is greater than 0.6. NCM (0.6≤x) can also be called "high nickel material". NCM (0.6≤x) contains, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, etc. "NCM (x < 0.6)" means that in the above formula "Li 1-a Ni x Co y Mn z O2", compounds with x (Ni ratio) less than 0.6. NCM (x<0.6) contains, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc. The mixing ratio (mass ratio) of NCM (0.6≤x) and NCM (x<0.6) may be, for example, "NCM (0.6≤x) / NCM (x<0.6) = 9 / 1 to 1 / 9", "NCM (0.6≤x) / NCM (x<0.6) = 9 / 1 to 4 / 6", and "NCM (0.6≤x) / NCM (x<0.6) = 9 / 1 to 3 / 7".

[0150] The positive electrode active material may also include, for example, NCA and NCM. The mixing ratio (mass ratio) of NCA and NCM may also be, for example, any one of "NCA / NCM=9 / 1 to 1 / 9", "NCA / NCM=9 / 1 to 4 / 6" and "NCA / NCM=9 / 1 to 3 / 7". The Ni ratio between NCA and NCM may be the same or different. The Ni ratio of NCA may be higher than the Ni ratio of NCM. The Ni ratio of NCA may also be lower than the Ni ratio of NCM.

[0151] <Transition Metal Oxides (Space Group C2 / m)>

[0152] The transition metal oxide may include, for example, a crystal structure belonging to the space group C2 / m, etc. The transition metal oxide may be represented by, for example, the following formula.

[0153] Li2MO3

[0154] In the above formula, M may include at least one selected from Ni, Co, Mn and Fe. The positive electrode active material may include a mixture of LiMO2 (space group R-3m) and Li2MO3 (space group C2 / m). The positive electrode active material may include a solid solution of LiMO2 and Li2MO3 (Li2MO3-LiMO2), etc.

[0155] <Transition Metal Oxides (Space Group Fd-3m)>

[0156] The transition metal oxide may include, for example, a crystal structure belonging to the space group Fd-3m, etc. The transition metal oxide may be represented by, for example, the following formula.

[0157] LiMn 2-x M x O4

[0158] In the above formula, the relationship of 0≤x≤2 is satisfied. M may include, for example, at least one selected from the group consisting of Ni, Fe, and Zn.

[0159] LiM2O4 (space group Fd-3m) may also contain, for example, LiMn2O4 and LiMn 1.5 Ni 0.5 At least one of O4. The positive electrode active material may also include a mixture of LiMO2 (space group R-3m) and LiM2O4 (space group Fd-3m). The mixing ratio (mass ratio) of LiMO2 (space group R-3m) and LiM2O4 (space group Fd-3m) may be, for example, any one of "LiMO2 / LiM2O4=9 / 1 to 9 / 1", "LiMO2 / LiM2O4=9 / 1 to 5 / 5" and "LiMO2 / LiMO4=9 / 1 to 7 / 3".

[0160] <Polyanionic compounds>

[0161] The polyanion compound may include, for example, phosphate (eg, LiFePO 4 , etc.), silicate, borate, etc. The polyanion compound may also be represented by, for example, the following formulas.

[0162] LiMPO4

[0163] Li 2-x MPO4F

[0164] Li2MSiO4

[0165] LiMBO3

[0166] In the above formulas, M may include at least one selected from Fe, Mn and Co. 2-x In "MPO4F", for example, the relationship of 0≤x≤2 may also be satisfied.

[0167] The positive electrode active material may also include, for example, a mixture of LiMO2 (space group R-3m) and a polyanion compound. The mixing ratio (mass ratio) of LiMO2 (space group R-3m) and the polyanion compound may be, for example, "LiMO2 / polyanion compound = 9 / 1 to 9 / 1", "LiMO2 / polyanion compound = 9 / 1 to 5 / 5" or "LiMO2 / polyanion compound = 9 / 1 to 7 / 3".

[0168] <Dopant>

[0169] Dopants may also be added to the positive electrode active material. The dopant may be diffused throughout the particle or locally distributed. For example, the dopant may be unevenly present on the particle surface. The dopant may be a substitutional solid solution atom or an interstitial solid solution atom. The amount of dopant added (relative to the molar fraction of the entire positive electrode active material) may be, for example, any one of 0.01 to 5%, 0.1 to 3%, and 0.1 to 1%. One or more dopants may be added. Two or more dopants may also form a composite.

[0170] The dopant may, for example, include at least one selected from B, C, N, halogen, Si, Na, Mg, Al, Mn, Co, Cr, Sc, Ti, V, Cu, Zn, Ga, Ge, Se, Sr, Y, Zr, Nb, Mo, In, Pb, Bi, Sb, Sn, W, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and actinide elements.

[0171] For example, the group of "Zr, Mg, W, Sm", the group of "Ti, Mn, Nb, Si, Mo", or the group of "Er, Mg" may be added to NCA. For example, Ti may be added to NCM. For example, the group of "Zr, W", the group of "Si, W", or the group of "Zr, W, Al, Ti, Co" may be added to NCM.

[0172] <Surface Covering>

[0173] The positive electrode active material may also form composite particles. The composite particles may, for example, also include core particles and a covering layer. The core particles include the positive electrode active material. The covering layer covers at least a portion of the surface of the core particle. The thickness of the covering layer may, for example, be any one of 1 to 3000 nm, 5 to 2000 nm, 10 to 1000 nm, 10 to 100 nm, and 10 to 50 nm. The thickness of the covering layer may be measured, for example, in an SEM image of a particle cross section. That is, a sample is prepared by embedding the composite particles in a resin material. The sample is subjected to cross-section exposure processing by an ion milling device. The cross section of the sample is observed by SEM. For 10 composite particles, the thickness of the covering layer is measured in 20 viewing fields respectively. The arithmetic mean of the thickness at a total of 200 locations is used.

[0174] The ratio of the portion of the surface of the core particle covered by the coating layer is also referred to as "coverage". The coverage rate may be, for example, 1% or more, 10% or more, 30% or more, 50% or more, or 70% or more. The coverage rate may be, for example, 100% or less, 90% or less, or 80% or less.

[0175] The coverage can be measured, for example, by XPS (X-ray Photoelectron Spectroscopy). A powder sample consisting of composite particles is placed on XPS. A narrow scan analysis is performed. The measurement data is processed by analysis software. By analyzing the measurement data, a variety of elements are detected. The ratio of each detected element is calculated based on the area of ​​each peak. The coverage is calculated according to the following formula.

[0176] γ={I1 / (I0+I1)}×100

[0177] γ: Coverage [%]

[0178] I0: Ratio of elements from nuclear particles

[0179] I1: Ratio of elements from the overlay

[0180] For example, when the core particle includes NCM, I0 represents the total element ratio of "Ni, Co, Mn". For example, when the core particle includes NCA, I0 represents the total element ratio of "Ni, Co, Al". For example, when the cover layer includes P and B, I1 represents the total element ratio of "P, B".

[0181] The covering layer may contain optional components. For example, the covering layer may also contain a simple substance, an organic substance, an inorganic acid salt, an organic acid salt, a hydroxide, an oxide, a carbide, a nitride, a sulfide, a halide, and the like. The covering layer may, for example, also include at least one selected from B, Al, W, Zr, Ti, Co, F, lithium compounds (such as Li2CO3, LiHCO3, LiOH, Li2O, etc.), tungsten oxide (such as WO3, etc.), titanium oxide (such as TiO2, etc.), zirconium oxide (such as ZrO2, etc.), boron oxide, boron phosphate (such as BPO4, etc.), aluminum oxide (such as Al2O3, etc.), boehmite, aluminum hydroxide, phosphate [such as Li3PO4, (NH4)3PO4, AlPO4, etc.], borate (such as Li2B4O7, LiBO3, etc.), polyacrylate (Li salt, Na salt, NH4 salt, etc.), acetate (such as Li salt, etc.), CMC (CMC-Na, CMC-Li, CMC-NH4, etc.), LiNbO3, Li2TiO3 and Li-containing halide (such as LiAlCl4, LiTiAlF6, LiYBr6, LiYCl6, etc.).

[0182] <Hollow Particles / Solid Particles>

[0183] Both hollow particles and solid particles are secondary particles. In the cross-sectional image of a "hollow particle", the proportion of the hollow area in the center is more than 30% of the cross-sectional area of ​​the entire particle. The proportion of the hollow in a hollow particle may be, for example, 40%, more than 50%, and more than 60%. In the cross-sectional image of a "solid particle", the proportion of the hollow area in the center is less than 30% of the cross-sectional area of ​​the entire particle. The proportion of the hollow in a solid particle may be, for example, less than 20%, less than 10%, and less than 5%. The positive electrode active material may be a hollow particle or a solid particle. A mixture of hollow particles and solid particles may also be used. The mixing ratio (mass ratio) of hollow particles and solid particles can be, for example, any one of "hollow particles / solid particles = 1 / 9 to 9 / 1", "hollow particles / solid particles = 2 / 8 to 8 / 2", "hollow particles / solid particles = 3 / 7 to 7 / 3" and "hollow particles / solid particles = 4 / 6 to 6 / 4".

[0184] <Large Particles / Small Particles>

[0185] "Electrode active material" is a general term for positive electrode active materials and negative electrode active materials. Electrode active materials may have, for example, a unimodal particle size distribution (based on the number of particles). Electrode active materials may also have, for example, a multimodal particle size distribution. Electrode active materials may also have, for example, a bimodal particle size distribution. That is, electrode active materials may also contain large particles and small particles. When the particle size distribution is bimodal, the particle size corresponding to the peak of the larger particle size is regarded as the particle size of the large particle (d L The particle size corresponding to the peak top of the smaller particle size is regarded as the particle size of the small particle (d S ). Particle size ratio (d L / d S ) can be, for example, any one of 2 to 10, 2 to 5, and 2 to 4. For example, d L It may be any one of 8 to 20 μm and 8 to 15 μm. S For example, the thickness may be any one of 1 to 10 μm and 1 to 5 μm.

[0186] For example, the particle size distribution can also be subjected to peak separation processing using waveform analysis software. The peak area (S L ) and the peak area from small particles (S S ) can be, for example, "S L / S S =1 / 9~9 / 1", "S L / S S =5 / 5~9 / 1" and "S L / S S = Any one of 7 / 3 to 9 / 1".

[0187] The particle size distribution based on the number is measured by microscopy. A plurality of cross-sectional samples are prepared from the electrode active material layer. The cross-sectional sample may also include a cross-section perpendicular to the surface of the electrode active material layer. For example, the surface of the observation object is cleaned by ion milling or the like. The cross-sectional sample is observed by SEM. The observation magnification is adjusted so that 10 to 100 particles are included in the observation field. The Feret diameter of all particles in the image is measured. "Ferret diameter" indicates the distance between the two farthest points on the contour line of the particle. By observing a plurality of cross-sectional samples, a total of more than 1000 Feret diameters are obtained. A particle size distribution based on the number is prepared based on more than 1000 Feret diameters.

[0188] A bimodal particle size distribution can be formed by mixing two kinds of particles. The two kinds of particles have different particle size distributions. For example, the two kinds of particles may have different D50s. For example, the D50 of large particles may be any one of 8 to 20 μm and 8 to 15 μm. For example, the D50 of small particles may be any one of 1 to 10 μm and 1 to 5 μm. The ratio of the D50 of large particles to the D50 of small particles may be, for example, any one of 2 to 10, 2 to 5, and 2 to 4. The mixing ratio (mass ratio) of large particles and small particles may be, for example, any one of "large particles / small particles = 1 / 9 to 9 / 1", "large particles / small particles = 5 / 5 to 9 / 1", and "large particles / small particles = 7 / 3 to 9 / 1".

[0189] Furthermore, the large particles and the small particles may have the same composition or different compositions. For example, the large particles may be NCA and the small particles may be NCM. For example, the large particles may be NCM (0.6≤x) and the small particles may be NCM (x<0.6).

[0190] <Electrolyte>

[0191] The electrolyte is a liquid electrolyte. The electrolyte contains a solute and a solvent. The concentration of the solute may be, for example, any one of 0.5 to 1 mol / L, 1 to 1.5 mol / L, 1.5 to 2 mol / L, 2 to 2.5 mol / L, and 2.5 to 3 mol / L. "mol / L" is sometimes expressed as "M". The solute contains a supporting salt (Li salt). The solute may also contain, for example, an inorganic acid salt, an imide salt, an oxalate complex, a halide, and the like. The solute may, for example, include at least one selected from LiPF6, LiBF4, LiClO4, LiAsF6, LiSbF6, LiN(SO2F)2 "LiFSI", LiN(SO2CF3)2 "LiTFSI", LiB(C2O4)2 "LiBOB", LiBF2(C2O4) "LiDFOB", LiPF2(C2O4)2 "LiDFOP", LiPO2F2, FSO3Li, LiI, LiBr and their derivatives.

[0192] The electrolyte may also include, for example, a carbonate-based solvent (carbonate ester-based solvent). The solvent may also include, for example, a cyclic carbonate, a chain carbonate, a fluorinated carbonate, etc. The solvent may also include, for example, at least one selected from ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (FEC), difluoroethylene carbonate, 4,4-difluoroethylene carbonate, trifluoroethylene carbonate, perfluoroethylene carbonate, fluoropropylene carbonate, difluoropropylene carbonate, and derivatives thereof.

[0193] The solvent may also include cyclic carbonates (EC, PC, FEC, etc.) and chain carbonates (EMC, DMC, DEC, etc.). The mixing ratio (volume ratio) of cyclic carbonates and chain carbonates may be, for example, any one of "cyclic carbonate / chain carbonate=1 / 9 to 4 / 6", "cyclic carbonate / chain carbonate=2 / 8 to 3 / 7", and "cyclic carbonate / chain carbonate=3 / 7 to 4 / 6".

[0194] The solvent may also contain cyclic carbonates (EC, PC, etc.) and fluorinated cyclic carbonates (FEC, etc.). The mixing ratio (volume ratio) of cyclic carbonates and fluorinated cyclic carbonates may be, for example, any one of "cyclic carbonate / fluorinated cyclic carbonate=99 / 1 to 90 / 10", "cyclic carbonate / fluorinated cyclic carbonate=9 / 1 to 1 / 9", "cyclic carbonate / fluorinated cyclic carbonate=9 / 1 to 7 / 3" and "cyclic carbonate / fluorinated cyclic carbonate=3 / 7 to 1 / 9".

[0195] The solvent may contain, for example, EC, FEC, EMC, DMC, and DEC. The volume ratio of each component may satisfy the relationship represented by the following formula, for example.

[0196] V EC +V FEC +V EMC +V DMC +V DEC =10

[0197] In the above formula, V EC 、V FEC 、V EMC 、V DMC 、V DEC They represent the volume ratios of EC, FEC, EMC, DMC and DEC respectively.

[0198] The following relations are satisfied:

[0199] 1≤V EC ≤4, 0≤V FEC ≤3, V EC +V FEC ≤4,

[0200] 0≤V EMC ≤9, 0≤V DMC ≤9, 0≤V DEC ≤9, 6≤V EMC +V DMC +V DEC ≤9.

[0201] For example, 1≤V EC ≤2 or 2≤V EC The relationship is ≤3.

[0202] For example, 1≤V FEC ≤2 or 2≤V FEC The relationship is ≤4.

[0203] For example, 3≤V EMC ≤4 or 6≤V EMC The relationship is ≤8.

[0204] For example, 3≤V DMC ≤4 or 6≤V DMC The relationship is ≤8.

[0205] For example, 3≤V DEC ≤4 or 6≤V DEC The relationship is ≤8.

[0206] The solvent may have, for example, a composition such as "EC / EMC=3 / 7", "EC / DMC=3 / 7", "EC / FEC / DEC=1 / 2 / 7", "EC / DMC / EMC=3 / 4 / 3", "EC / DMC / EMC=3 / 3 / 4", "EC / FEC / DMC / EMC=2 / 1 / 4 / 3", "EC / FEC / DMC / EMC=1 / 2 / 4 / 3", "EC / FEC / DMC / EMC=2 / 1 / 3 / 4", "EC / FEC / DMC / EMC=1 / 2 / 3 / 4", etc., in terms of volume ratio.

[0207] The electrolyte solution may also contain an ether solvent. For example, the electrolyte solution may also contain a solvent selected from tetrahydrofuran (THF), 1,4-dihydrofuran (THF), At least one of oxane (DOX), 1,3-dioxolane (DOL), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), hydrofluoroether (HFE), ethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and derivatives thereof.

[0208] The electrolyte may also contain any additives. The amount of addition (relative to the mass fraction of the entire electrolyte) may be, for example, any one of 0.01% to 5%, 0.05% to 3%, and 0.1% to 1%. The additives may also include, for example, SEI (Solid Electrolyte Interphase) formation promoters, SEI formation inhibitors, gas generators, overcharge prevention agents, flame retardants, antioxidants, electrode protective agents, surfactants, etc.

[0209] The additive may include, for example, vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (PS), tert-amylbenzene, 1,4-di-tert-butylbenzene, biphenyl (BP), cyclohexylbenzene (CHB), ethylene sulfide (ES), propane sultone (PS), ethylene sulfide (DTD), γ-butyrolactone, phosphazene compounds, carboxylates [such as methyl formate (MF), methyl acetate (MA), methyl propionate (MP), propylene glycol (PEG ... diethyl diacid (DEM), etc.], fluorobenzenes [e.g. monofluorobenzene (FB), 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,3,5-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, 1,2,3,5-tetrafluorobenzene, 1,2,4,5-tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, etc.], fluorotoluenes (e.g. 2-fluorotoluene, 3-fluorotoluene, 4-fluorotoluene, 2,3-difluorotoluene, benzene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,6-difluorotoluene, 3,4-difluorotoluene, octafluorotoluene, etc.), trifluorotoluene (e.g. trifluorotoluene, 2-fluorotrifluorotoluene, 3-fluorotrifluorotoluene, 4-fluorotrifluorotoluene, 2-methyltrifluorotoluene, 3-methylbenzotrifluoride, 4-methylbenzotrifluoride, etc.), fluoroxylene (e.g. 3-fluoro-o-xylene, 4-fluoro-o-xylene, 2-fluoro-m-xylene, 5-fluoro-m-xylene The invention can be used in the following embodiments: the present invention can be used to prepare at least one of the following compounds: 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 51, 52, 53, 54, 55, 56, 57, 58, 59, 61, 62, 63, 64, 65, 67, 68, 69, 71, 72, 73, 74, 75, 76, 77, 78, 79, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 101, 102, 114, 115, 126, 133, 134, 147, 159, 119, 129, 135, 148, 15

[0210] The above components as solute and solvent may also be used as trace components (additives). The additive may include, for example, at least one selected from LiBF4, LiFSI, LiTFSI, LiBOB, LiDFOB, LiDFOP, LiPO2F2, FSO3Li, LiI, LiBr, HFE, DOX, PC, FEC and their derivatives.

[0211] The electrolyte may also contain an ionic liquid. The ionic liquid may also contain, for example, a sulfonium salt, an ammonium salt, a pyridinium salt, a piperidinium salt, a pyrrolidine salt, a morpholinium salt, Salt, imidazole At least one of salts and derivatives thereof.

[0212] <Gel Electrolyte>

[0213] The battery 1000 may also include a gel electrolyte. The gel electrolyte may also include an electrolyte solution and a polymer material. The polymer material may also form a polymer matrix. The polymer material may also include at least one selected from PVdF, PVdF-HFP, PAN, PVdF-PAN, polyethylene oxide (PEO), polyethylene glycol (PEG) and derivatives thereof.

[0214] <Diaphragm>

[0215] The separator 300 can separate the positive electrode from the negative electrode. The separator 300 has electrical insulation. The separator 300 may also include, for example, at least one selected from a resin film, an inorganic particle layer, and an organic particle layer. The separator 300 may also include, for example, a resin film and an inorganic particle layer.

[0216] The resin film is porous. The resin film may also include, for example, a microporous film, a nonwoven fabric, etc. The resin film includes a resin skeleton. The resin skeleton may also be continuous in a network, for example. Pores are formed in the gaps of the resin skeleton. The resin film allows electrolytes to pass through. The average pore size of the resin film may also be, for example, less than 1 μm. The average pore size of the resin film may also be, for example, 0.01 to 1 μm or 0.1 to 0.5 μm. The "average pore size" may be measured by mercury intrusion. The Gurley value of the resin film may also be, for example, 50 to 250 s / 100 cm 3 The "Gerard value" can be determined by the Gerard value test method.

[0217] The resin film may include, for example, at least one selected from olefin resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, acrylic resins, and polyester resins. The resin film may include, for example, at least one selected from polyethylene (PE), polypropylene (PP), polyamide (PA), polyamideimide (PAI), polyimide (PI), aromatic polyamide (aramid), polyphenylene ether (PPE), and derivatives thereof. The resin film may be formed, for example, by a stretching method, a phase separation method, and the like. The thickness of the resin film may be, for example, any one of 5 to 50 μm and 10 to 25 μm.

[0218] The resin film may have a single-layer structure, for example. The resin film may also be composed of a PE layer, for example. The skeleton of the PE layer is formed by PE. The PE layer may have a shutdown function. The resin film may also have a multi-layer structure, for example. The resin film may also include a PP layer and a PE layer, for example. The skeleton of the PP layer is formed by PP. The resin film may also have a three-layer structure, for example. The resin film may also be formed by stacking a PP layer, a PE layer and a PP layer in sequence. The thickness of the PE layer may also be, for example, 5 to 20 μm. The thickness of the PP layer may also be, for example, 3 to 10 μm.

[0219] The inorganic particle layer may also be formed on the surface of the resin film. The inorganic particle layer may be formed only on one side of the resin film, or may be formed on both sides. The inorganic particle layer may be formed on the side opposite to the positive electrode, or may be formed on the side opposite to the negative electrode. Furthermore, the inorganic particle layer may be formed on the surface of the positive electrode, or may be formed on the surface of the negative electrode.

[0220] The inorganic particle layer is porous. The inorganic particle layer contains inorganic particles. The inorganic particles can also be called "inorganic filler". Pores are formed in the gaps between the inorganic particles. The thickness of the inorganic particle layer can also be, for example, any one of 0.5 to 10 μm and 1 to 5 μm. The inorganic particles can also contain heat-resistant materials, for example. The inorganic particle layer containing heat-resistant materials is also called "HRL (Heat Resistance Layer)". The inorganic particles can also contain at least one selected from boehmite, aluminum oxide, zirconium oxide, titanium oxide, magnesium oxide and silicon oxide. The inorganic particles can have any shape. The inorganic particles can also be, for example, spherical, rod-shaped, plate-shaped, fibrous, etc. The D50 of the inorganic particles can also be, for example, any one of 0.1 to 10 μm and 0.5 to 3 μm. The inorganic particle layer can also contain a binder. The binder can also contain, for example, at least one selected from acrylic resins, polyamide resins, fluorine resins, aromatic polyether resins and liquid crystal polyester resins.

[0221] The diaphragm 300 may include, for example, an organic particle layer. The diaphragm 300 may include, for example, an organic particle layer instead of a resin film. The diaphragm 300 may include, for example, an organic particle layer instead of an inorganic particle layer. The diaphragm 300 may include both a resin film and an organic particle layer. The diaphragm 300 may include both an inorganic particle layer and an organic particle layer. The diaphragm 300 may include a resin film, an inorganic particle layer, and an organic particle layer.

[0222] The thickness of the organic particle layer may be, for example, any one of 0.1 to 50 μm, 0.5 to 20 μm, 0.5 to 10 μm, and 1 to 5 μm. The organic particle layer contains organic particles. The organic particles may also be referred to as "organic fillers". The organic particles may also contain heat-resistant materials. The organic particles may also contain, for example, at least one selected from PE, PP, PTFE, PI, PAI, PA, and aromatic polyamide. The organic particles may also be, for example, spherical, rod-shaped, plate-shaped, fibrous, and the like. The D50 of the organic particles may also be, for example, any one of 0.1 to 10 μm and 0.5 to 3 μm.

[0223] The separator 300 may include, for example, a mixed layer. The mixed layer includes both inorganic particles and organic particles.

[0224] <Battery structure>

[0225] Figure 7 This is a table showing the structure of the first battery. Figure 8 This is a table showing the structure of the second battery. Fig. 9 It is a table showing the third battery structure. In each table, when a cell records multiple materials, the record includes each material alone and their combination. For example, when a cell records "α, β, γ" materials, the record means "at least one selected from α, β and γ". Any elements can be extracted from each of the first battery structure, the second battery structure and the third battery structure, and can also be combined arbitrarily.

[0226] [Example]

[0227] <Production of test unit>

[0228] Fig.10 TABLE 1 Test cells (monopolar cells) No. 1 to No. 18 were manufactured in the following procedure.

[0229] Negative electrode manufacturing

[0230] Prepare the following materials.

[0231] Graphite: Artificial graphite (D50: 22μm, aspect ratio: reference Fig.10 )

[0232] Binder: SBR

[0233] Tackifier: CMC

[0234] Dispersion medium: water

[0235] Substrate: Cu foil (thickness: 15μm)

[0236] (a) Formation of the first layer

[0237] The first slurry is prepared by mixing graphite, a binder, a thickener, and a dispersion medium. The solid content ratio is "graphite / binder / thickener = 98.4 / 1.2 / 0.4 (mass ratio)". That is, the binder ratio in the first slurry is 1.2. The viscosity of the first slurry is adjusted to 25000 mPa·s. The first slurry is applied to the substrate by a scraper to form the first layer.

[0238] (b) Formation of the second layer

[0239] The second slurry is prepared by mixing graphite, a binder, a thickener and a dispersion medium. The solid content ratio is "graphite / binder / thickener = 97.8 / 1.8 / 0.4 (mass ratio)". That is, the binder ratio in the second slurry is 1.8. The viscosity of the second slurry is adjusted to 12000 mPa·s. The second slurry is applied to the first slurry by a scraper to form a second layer.

[0240] (c) Magnetic field orientation

[0241] A magnetic field was applied to the coatings (layer 1 and layer 2) for 10 minutes.

[0242] (d) Drying

[0243] The coating was dried at 50° C. to form a negative electrode active material layer.

[0244] (e) Compression

[0245] The negative electrode active material layer was compressed. After compression, the density of the negative electrode active material layer was 1.25 g / cm 3 The thickness of the negative electrode active material layer is Fig.10 The unit area weight of the first layer is 7 mg / cm 2 The unit area weight of the second layer is 20 mg / cm 2 .

[0246] The negative electrode was manufactured through the above steps. XRD measurement of the negative electrode was performed. In the cross section of the negative electrode active material layer, the orientation angle of each layer was measured.

[0247] Preparation of positive electrode

[0248] Prepare the following materials.

[0249] Positive electrode active material: LiNi 0.8 Co 0.1 Mn 0.1 O2

[0250] Conductive material: CNT

[0251] Adhesive: PVdF

[0252] Dispersion medium: N-methyl-pyrrolidone

[0253] Substrate: Al foil (thickness: 30 μm)

[0254] The slurry is prepared by mixing the positive electrode active material, the conductive material, the binder and the dispersion medium. The solid content ratio is "positive electrode active material / conductive material / binder = 97.8 / 0.8 / 1.4 (mass ratio)". The slurry is applied to the substrate by a scraper to form a positive electrode active material layer. The positive electrode active material layer is dried. The drying temperature is 90°C and the drying time is 10 minutes. The positive electrode is manufactured by compressing the positive electrode active material layer. After compression, the density of the positive electrode active material layer is 3.3g / cm 3 The weight per unit area of ​​the positive electrode active material layer was adjusted so that the ratio of the negative electrode capacity to the positive electrode capacity became 1.1.

[0255] Assembly

[0256] Prepare the following materials.

[0257] Diaphragm: three-layer structure (PP layer / PE layer / PP layer), thickness: 16μm

[0258] Electrolyte: 1.1M LiPF6, EC / DMC / EMC=3 / 4 / 3 (volume ratio)

[0259] Outer body: Al laminated film soft package

[0260] The positive electrode, the separator, and the negative electrode were sequentially stacked to form a power generating element, and the power generating element was sealed in an outer casing to produce a test cell.

[0261] <Charge and discharge test>

[0262] Activation treatment

[0263] As the initial charge, a constant current-constant voltage method is used for charging. That is, a constant current charge is performed at a current of 0.1C until 4.25V is reached. After reaching 4.25V, a constant voltage charge is performed for 3 hours. After the charge is completed, a constant current discharge is performed at a current of 0.1C until 3.0V is reached. "C" is a symbol indicating the time rate of the current. A current of 1C discharges the theoretical capacity of the test unit in 1 hour.

[0264] Determination of discharge rate

[0265] A constant current charge was performed at 0.1C until 4.25V was reached. After reaching 4.25V, a constant voltage charge was performed for 3 hours. After charging, a constant current discharge was performed at 1C until 3.0V was reached, and the discharge capacity was measured. The discharge rate was calculated by dividing the discharge capacity by the theoretical capacity.

[0266] <Results>

[0267] exist Fig.10 When the relationships of the following formulae (1) to (3) are satisfied, a tendency for the discharge rate to be high is observed.

[0268] 1.2≤A≤4 (1)

[0269] 1 <m2 / m1 (2)

[0270] 1<θ2 / θ1 (3)

[0271] Furthermore, in Fig.10 In the "orientation angle ratio" item, "">1" means that "θ2 / θ1" exceeds 1. Fig.10 In the table, the samples satisfying the above formulas (1) to (3) are marked with "*" in No. (number).

[0272] Fig.11 This is a graph showing the relationship between the XRD intensity ratio and the discharge rate. As the XRD intensity ratio increases, the discharge rate tends to increase. When the XRD intensity ratio is 0.02 or more, the discharge rate tends to increase easily.

[0273] Fig.12 It is a coordinate diagram showing the relationship between the aspect ratio of graphite and the discharge rate. If the aspect ratio exceeds 4, it can be seen that the discharge rate is difficult to improve. It is believed that this is affected by the cracking of particles during pressing. When the aspect ratio is less than 1.2, it can also be seen that the discharge rate is difficult to improve.< / nca> < / ncm>

Claims

1. A battery electrode, comprising a substrate and a negative electrode active material layer, The negative electrode active material layer is disposed on the surface of the substrate. The negative electrode active material layer comprises graphite and a binder, A first layer and a second layer are formed in the negative electrode active material layer, The first layer is formed between the substrate and the second layer, Satisfying the relationship between equations (1) to (3), 1.2≤A≤4 (1) 1 <m2 / m1 (2) 1<θ2 / θ1 (3) In the above formulas (1) to (3), A represents the aspect ratio of the graphite, m1 represents the mass fraction of the binder in the first layer, m2 represents the mass fraction of the adhesive in the second layer, θ1 represents the orientation angle of the graphite in the first layer, and, θ2 represents the orientation angle of the graphite in the second layer.

2. The battery electrode according to claim 1, Further satisfying the relationship of formula (4), 0.02≤I 110 / I 002 (4) In the formula (4), I 110 represents the diffraction intensity of the (110) plane in the X-ray diffraction pattern of the negative electrode active material layer, and I 002 It represents the diffraction intensity of the (002) plane in the X-ray diffraction pattern of the negative electrode active material layer.

3. The battery electrode according to claim 1 or 2, The thickness of the negative electrode active material layer is 100 to 400 μm.

4. The battery electrode according to claim 1 or 2, Further satisfying the relationship of formula (5), 0.1≤T1 / (T1+T2)≤0.4 (5) In the formula (5), T1 represents the thickness of the first layer, and T2 represents the thickness of the second layer.

5. A battery comprising the battery electrode according to claim 1 or 2.

6. A method for manufacturing a battery electrode, comprising the following steps in sequence: Step (a): forming a first layer by coating a first slurry on a surface of a substrate; Step (b): forming a second layer by coating a second slurry on the first layer; Step (c): applying a magnetic field to the first layer and the second layer; and Step (d): forming a negative electrode active material layer by drying the first layer and the second layer, wherein the first slurry and the second slurry respectively contain graphite, a binder and a dispersion medium, Satisfying the relationship between equations (6) and (7), 2<η1 / η2 (6) 1<r2 / r1 (7) In the formula (6) and formula (7), η1 represents the viscosity of the first slurry, η2 represents the viscosity of the second slurry, r1 represents the mixing ratio of the binder in the solid content of the first slurry, and r2 represents the mixing ratio of the binder in the solid content of the second slurry.

Citation Information

Patent Citations

  • Power storage device and secondary battery

    JP2014096201A